2016
DOI: 10.1037/sgd0000147
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the closet: Differentiating stigma concealment and nondisclosure processes.

Abstract: Individuals with concealable stigmatized identities face many options regarding whether, when, how, and to whom to conceal or disclose information about their marginalized social status. Numerous studies have examined the psychosocial health consequences of different stigma concealment and disclosure processes, but research in this area is hindered by a relative lack of attention to potential differences among these stigma management variables. The present research investigated the distinctness of stigma manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 59 publications
(153 reference statements)
3
122
0
7
Order By: Relevance
“…Underpinning this finding, Kosciw et al (2012) reported, after examining a sample of sexual minority high school students, that being more out to one's environment was significantly related to higher levels of self-esteem. Recent evidence from Jackson and Mohr (2016) is in line with the body of these findings, suggesting that there is a significant association between concealing one's sexual orientation and higher levels of self-stigma, lower life satisfaction, as well as lower levels of identity strength. Contradictory to the supporting evidence, other studies (Russell & Joyner, 2001;Diamond & Lucas, 2004) have found that although sexual minority youth may have positive, accepting, and nurturing environments, they may still present lower self-esteem because of internalized issues with peer group belonging.…”
Section: Family and Friendssupporting
confidence: 59%
“…Underpinning this finding, Kosciw et al (2012) reported, after examining a sample of sexual minority high school students, that being more out to one's environment was significantly related to higher levels of self-esteem. Recent evidence from Jackson and Mohr (2016) is in line with the body of these findings, suggesting that there is a significant association between concealing one's sexual orientation and higher levels of self-stigma, lower life satisfaction, as well as lower levels of identity strength. Contradictory to the supporting evidence, other studies (Russell & Joyner, 2001;Diamond & Lucas, 2004) have found that although sexual minority youth may have positive, accepting, and nurturing environments, they may still present lower self-esteem because of internalized issues with peer group belonging.…”
Section: Family and Friendssupporting
confidence: 59%
“…Given that women generally indicated that they did not try to conceal their sexual histories, interventions that focus on disclosure to providers may be misplaced, in light of work suggesting that it is concealment (which may be motivated by internalized homophobia) that has the most negative effects on well-being (Dyar et al, 2015; Jackson & Mohr, 2016). And yet, efforts to facilitate disclosure (e.g., via affirming environmental cues) may be beneficial, in that providers are better equipped to offer appropriate referrals if they know patients’ sexual histories.…”
Section: Discussionmentioning
confidence: 99%
“…En consecuencia, se espera que un grupo de personas no conformes con la propia orientación sexual intente ocultarla o disimularla lo mejor 60,61 . Sin duda, este proceso de encubrimiento es más eficaz cuando existe mayor congruencia con el género esperado y, por lo tanto, se asume que el género es completamente armónico con la orientación sexual esperada, es decir, heterosexual 62 .…”
Section: Discussionunclassified